Fish community reassembly after a coral mass mortality: higher trophic groups are subject to increased rates of extinction - Alonso, David; Pinyol-Gallemí, Aleix; Alcoverro, Teresa; Arthur, Rohan (Ecology letters, 2015)
Since Gleason and Clements, our understanding of community dynamics has been influenced by theories emphasising either dispersal or niche assembly as central to community structuring. Determining the relative importance of these processes in structuring real‐world communities remains a challenge. We tracked reef fish community reassembly after a catastrophic coral mortality in a relatively unfished archipelago. We revisited the stochastic model underlying MacArthur and Wilson's Island Biogeography Theory, with a simple extension to account for trophic identity. Colonisation and extinction rates calculated from decadal presence‐absence data based on (1) species neutrality, (2) trophic identity and (3) site‐specificity were used to model post‐disturbance reassembly, and compared with empirical observations. Results indicate that species neutrality holds within trophic guilds, and trophic identity significantly increases overall model performance. Strikingly, extinction rates increased clearly with trophic position, indicating that fish communities may be inherently susceptible to trophic downgrading even without targeted fishing of top predators.